Comparative cytogenetics of spiny rats of the genus proechimys (Rodentia, Echimyidae) from the Amazon region - Eler, Eduardo Schmidt (2012)
We made a comparative analysis of the cytogenetics of spiny rat species of the genus Proechimys collected from several sites of the Madeira River basin (Amazonas State, Brazil) and Jari River valley (Pará State, Brazil). Individuals were assigned to three groups based on diploid and fundamental numbers: 2n=28, FN=46 (P. cuvieri and P. gr. longicaudatus); 2n=38, FN=52 (Proechimys gr. guyannensis), and 2n=40, FN=54 (P. gardneri). The nucleolar organizer region (NOR) was interstitial on the long arm of one submetacentric pair, as seen in all species of Proechimys analyzed thus far. However, its position in the karyotype was variable. A duplication of the NOR in one of the homologues was detected in P. gr. longicaudatus from the Aripuanã basin along the mid Madeira. The C-band pattern varied between species and, together with the NOR, allowed the identification of two evolutionary units in P. gr. longicaudatus in the region of the mid Madeira River (cytotypes A and B). The morphology and banding of the sex chromosomes were species specific. A range extension is suggested for the geographic distribution of P. gardneri and P. gr. longicaudatus. Moreover, we suggest that species of Proechimys with 2n=38 chromosomes are restricted to east of the Negro River and north of the Amazon River. We also revised the published chromosome data available for Proechimys. © FUNPEC-RP.